The prevalence of, and risk factors for, mycoplasma genitalium infection among infertile women in Ibadan: A cross-sectional study - Tinuade Adesola Ajani; Timothy A. Olusesan Oluwasola; Mustapha A. Ajani; Rasheed Ajani Bakare (Shahid Sadoughi University of Medical Sciences, 2017)
Background: The association of mycoplasma genitalium (M. genitalium) with infertility has been documented. The infections are asymptomatic and difficult to diagnose. Understanding the associated risk factors will help in facilitating better screening measures for at-risk groups. Objective: The aim was to determine the prevalence of, and risk factors for, M. genitalium infection among infertile women in Ibadan. Materials and Methods: In this cross-sectional study, 402 women (267 infertile and 135 fertile) referred to 2 hospitals in Ibadan between March and November 2015 were enrolled. Information was obtained, using structured questionnaire, on sociodemographic and behavioral characteristics of the respondents while endocervical swabs were obtained for detection of M. genitalium. MgPa gene was diagnosed using the conventional Polymerase chain reaction. Bands corresponding to 495kb were documented as positive for M. genitalium. Results: Among the infertile women, 43 (16.1%) had evidence of M. genitalium infection as against 3 (2.2%) of women without infertility (p<0.001). Associated risk factors included having more than one lifetime sexual partner (OR=10.13, 95% CI: 3.76-33.97); husbands having other sexual partners (OR=12.88, 95% CI: 2.08-90.63); being a serial monogamist (OR=6, 95% CI: 4.35-8.27) and low socio-economic status (OR=2.80, 95% CI: 1.28-6.10). No relationship exists between the previous history of sexually transmitted infections and M. genitalium. Conclusion: The risk factors for M. genitalium infection are similar to those peculiar to other sexually transmitted infections. Its routine screening should be incorporated into the current protocol for microbiological evaluation of infertile women.